By Fables Alone Literature and State Ideology in Late Eighteenth- and Early Nineteenth-Century Russia - Zorin, Andrei (Ars Rossica, 2014)
Academic Studies Press is proud to present this translation of Professor Andrei Zorin's seminal Kormya Dvuglavogo Orla. This collection of essays includes several that have never before appeared in English, including "The People's War: The Time of Troubles in Russian Literature, 1806-1807" and "Holy Alliances: V. A. Zhukovskii's Epistle 'To Emperor Alexander' and Christian Universalism."